2015
DOI: 10.1002/adsc.201400925
|View full text |Cite
|
Sign up to set email alerts
|

Gas–Liquid Segmented Flow Microfluidics for Screening Copper/TEMPO‐Catalyzed Aerobic Oxidation of Primary Alcohols

Abstract: Aerobic oxidation using a combination of copper salts and 2,2,6,6-tetramethylpiperidine Noxyl (TEMPO) represent useful tools for organic synthesis and several closely related catalyst systems have been reported. To gain further insights, these catalytic systems were evaluated in a gasliquid segmented flow device. The improvement of oxygen mass transfer has a significant influence on the turnover-limiting step. Hence, an improved catalytic system using copper(II) as copper source was implemented in a microreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…170 An improved protocol for the selective aerobic oxidation of primary alcohols by Cu(I)/TEMPO catalysis in micro flow was reported by Favre-Réguillon. 172 Kinetic studies revealed that oxygen showed a first order relationship, which indicates that a higher oxygen concentration could be beneficial. Therefore, the mixture of 9% O2 in N2 was exchanged for a pure oxygen feed.…”
Section: Transition Metal-catalyzed Aerobic Oxidation Processes In Comentioning
confidence: 99%
“…170 An improved protocol for the selective aerobic oxidation of primary alcohols by Cu(I)/TEMPO catalysis in micro flow was reported by Favre-Réguillon. 172 Kinetic studies revealed that oxygen showed a first order relationship, which indicates that a higher oxygen concentration could be beneficial. Therefore, the mixture of 9% O2 in N2 was exchanged for a pure oxygen feed.…”
Section: Transition Metal-catalyzed Aerobic Oxidation Processes In Comentioning
confidence: 99%
“…This limitation can be elegantly circumvented by the well-established homogeneous copper-catalyzed aerobic oxidation protocol developed by Stahl using a catalytic mixture of Cu(OTf) 2 , 2,2 0 -bipyridine, TEMPO, and NMI [49]. Similar reactor concepts as for the Pd-catalyzed protocol were used in order to test the feasibility of the copperbased system for continuous purposes [109,110]. Importantly, a stainless steel syringe pump and storage unit for the catalyst mixture caused severe problems since a significant drop in catalytic activity was observed [109].…”
Section: Homogeneous Catalysismentioning
confidence: 99%
“…Favre‐Réguillon et al. entwickelten eine Methode, die auf segmentiertem Gas‐flüssig‐Fluss in Perfluoralkoxy(PFA)‐Röhren beruht . Darüber hinaus untersuchten Stahl et al.…”
Section: Aerobe Oxidation Von C(sp3)‐h‐bindungenunclassified